Improved first order mean spherical approximation for simple fluids - Hlushak, S.; Trokhymchuk, A.; Nezbeda, I. (Condensed Matter Physics, 2011)
A perturbation approach based on the first-order mean spherical approximation (FMSA) is proposed. It consists in adopting a hard-sphere plus short-range attractive Yukawa fluid as the novel reference system, over which the perturbative solution of the Ornstein-Zernike equation is performed. A choice of the optimal range of the reference attraction is discussed. The results are compared against conventional FMSA/HS theory and Monte-Carlo simulation data for compressibility factor and vapor-liquid phase diagrams of the medium-ranged Yukawa fluid. Proposed theory keeps the same level of simplicity and transparency, as the conventional FMSA/HS approach does, but shows to be more accurate. Пропонується новий пiдхiд теорiї збурень на основi середньосферичного наближення першого по-рядку (ССНПП). Вiн полягає у використаннi твердосферної (ТС) рiдини Юкави в якостi базисної системи, на основi якої розв’язується рiвняння Орнштейна-Цернiке в рамках теорiї збурень. У роботi обговорюється вибiр оптимального параметра притягальної далекодiї базисної системи. Результати порiвнюються зi звичайною теорiєю ССНПП/ТС та моделюванням Монте-Карло, для коефiцiєнта стисливостi i фазової дiаграми рiдини Юкави. Запропонована теорiя зберiгає попереднiй рiвень простоти та прозоростi як i звичайне ССНПП/ТС, але є бiльш точною.